2015
DOI: 10.4172/2157-7471.1000313
|View full text |Cite
|
Sign up to set email alerts
|

Soil-borne and Compost-borne Aspergillus Species for Biologically Controlling Post-harvest Diseases of Potatoes Incited by Fusarium sambucinum and Phytophthora erythroseptica

Abstract: Nine isolates of Aspergillus spp., isolated from soil and compost were tested in vitro and in vivo for their antifungal activity against Fusarium sambucinum and Phytophthora erythroseptica, the causal agents of the Fusarium dry rot and pink rot of potato tubers. Tested using the dual culture method, the pathogen growth of F. sambucinum and P. erythroseptica was inhibited by 27 to 68% and 16 to 25% by all Aspergillus species, respectively. The highest inhibitory activity against both pathogens was induced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…In accordance, previous Tunisian studies have shown the effectiveness of Aspergillus and Penicillium genera, originally recovered from compost extracts and solarized soils [18,47], in controlling Pythium spp. [48], Fusarium spp., and Phytophthora erythroseptica the causal agents of watery rot, dry rot and pink rot, respectively [20]. Compost-associated Penicillium spp., Aspergillus spp., and Talaromyces assiutensis were also shown able to suppress black scurf and stem canker potato disease caused by R. solani [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, previous Tunisian studies have shown the effectiveness of Aspergillus and Penicillium genera, originally recovered from compost extracts and solarized soils [18,47], in controlling Pythium spp. [48], Fusarium spp., and Phytophthora erythroseptica the causal agents of watery rot, dry rot and pink rot, respectively [20]. Compost-associated Penicillium spp., Aspergillus spp., and Talaromyces assiutensis were also shown able to suppress black scurf and stem canker potato disease caused by R. solani [49].…”
Section: Discussionmentioning
confidence: 99%
“…Successful biocontrol of potato postharvest diseases, including Fusarium dry rot, was achieved using Pseudomonas spp., Enterobacter spp., Bacillus spp., Trichoderma spp, Aspergillus spp. [2,[15][16][17][18][19][20]. Furthermore, an interesting approach to post-harvest disease control that has gained attention is the use of biocontrol agents (BCAs) naturally associated to healthy plants or tubers.…”
Section: Introductionmentioning
confidence: 99%
“…Various Aspergillus species recovered from solarized soils and/or composts (A. niger, A. flavus, A. terreus, A. nidulans) have successfully suppressed potato postharvest diseases such as Pythium leak incited by Pythium ultimum tuber dry rot induced by F. sambucinum and pink rot caused by Phytophthora sp. [29][30][31][32]. Several studies have also pointed out the usefulness of bioactive metabolites from naturally plant-associated fungi.…”
Section: Introductionmentioning
confidence: 99%
“…and Aspergillus spp. [27,31,32]. It is interesting to seek for new bioactive compounds exhibiting antifungal activities from plant-associated fungi [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…were found to be active against Fusarium spp [12][13][14][15]. Biondi et al [16] demonstrated the ability of methanol extracts of the cyanobacterium Nostoc strain to suppress the mycelial growth of F. oxysporum, Penicillium expansum, Phytophthora cinnamomi, Rhizoctonia solani, Sclerotinia sclerotiorum, and Verticillium albo-atrum.…”
Section: Introductionmentioning
confidence: 99%